IDENTIFICATION OF THE SEA BASE OF ACEH ISLAND USING FISHFINDER COMPUTER WITH ECHO SOUNDER SYSTEM - Nurul Hamdi (INFOKUM, 2021)
This study will identify the seabed using a Fishfinder computer with an Echo Sounder System, by taking the output data from the tool. The GARMIN Fishfinder 160 Blue is one of the best echo sounders out there today. This tool is a simple echo sounder, this tool can only measure water depth in one ping. A good system is a system that can identify the profile of the seabed. Therefore, a tool that can work optimally is made to display the profile of the seabed by utilizing the results of measurements of seabed depth per ping. This GARMIN Fishfinder 160 Blue can display the contours of the seabed, but this tool works based on a Microcontroller and is displayed on an LCD (Liquid Crystal Display). Indonesia is known as an archipelagic country which is also known as a maritime or maritime country. Indonesia's marine area reaches 5.8 million km2. This sea area is equal to about 70% of the total area of Indonesia. This means that Indonesia's sea area is larger than its land area. The results of the tests carried out are software that is built from the results of the design as expected in terms of accuracy and describes the depth point, so that it can form a seabed profile with the scale made. From the results of testing the Echo Sounder tool (GARMIN Fishfinder 160 Blue) at rest, the measurement error is relatively very small, below 5%. This means that this tool can still be used for research purposes. During software testing, there was a delay (delay) in displaying the basic in situ profile, compared to the GARMIN Fishfinder 160 Blue. Data retrieval of water depth when moving past 4 (four) points has the same value of water depth at 4 (four) points which have been previously measured using Hyperterminal..